The impact of maternal serum biomarkers on maternal and neonatal outcomes in twin pregnancies: a retrospective cohort study conducted at a tertiary hospital - Wu,Hanglin; Yu,Liming; Xie,Zhen; Cai,Hongxia; Wen,Caihe (PeerJ, 2024)
Background Prior prediction models used for screening preeclampsia (PE) in twin pregnancies were found to be inadequate. In singleton pregnancies, various maternal biomarkers have been shown to be correlated with negative pregnancy outcomes. However, the impact of these biomarkers in twin pregnancies remained uncertain. Methods A retrospective cohort study was carried out on 736 twin pregnancies at a tertiary hospital in Hangzhou, China. Multivariable logistic models were employed to examine the association between levels of serological markers and the likelihood of adverse pregnancy outcomes. The final logistic model was formulated as a user-friendly nomogram. The primary outcome assessed was the occurrence of PE. Results were presented as odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Results The prevalence of PE in the study was 10.3%. When comparing women diagnosed with PE to those without, it was evident that the former group experienced a significantly higher risk of unfavorable maternal and neonatal outcomes. A multivariable logistic regression analysis revealed notable associations between various factors including maternal age, parity, gestational weight gain, a family history of hypertension, as well as levels of cholesterol, albumin, and creatinine and the risk of developing PE, with a significance level of P < 0.05. The concordance index for the constructed nomogram was determined to be 0.792 (95% CI: [0.739–0.844]). Furthermore, an increment of 1 * 1012/L in red blood cell (RBC) count was associated with more than a two-fold increase in the odds of experiencing adverse maternal outcomes (OR 2.247, 95% CI: [1.229–4.107]). However, no significant correlations were identified between any of the examined variables and neonatal outcomes. Conclusions In this study, we developed a user-friendly predictive model that achieves notable detection rates by incorporating maternal serum biomarker levels alongside maternal characteristics and medical history. Our findings indicate that the probability of adverse maternal outcomes increases with elevated levels of RBCs. Obstetricians should consider intensifying surveillance for these women in clinical practice.
Keywords: Twin pregnancies; Preeclampsia; Serum biomarker; Risk factor; Multivariable logistic model